Pengetahuan Remaja Putri tentang Pemeriksaan Payudara Sendiri (SADARI): Knowledge of Young Women about Breast Self-Examination (BSE) - Windayanti, Hapsari; Adimayanti, Eka; Siyamti, Dewi (Universitas Ngudi waluyo, 2023)
In young women there is a very important stage of development, namely biological and physiological development which can determine the quality of oneself to become an adult. Menstruation is one indicator of female sexual maturity. During the menstrual cycle, it is necessary to pay attention to personal hygiene during menstruation and handling menstrual pain. In addition to this during the menstrual cycle there are things that are also of concern to adolescents, namely early detection of breast cancer, because young age is not a guarantee of being safe from breast cancer. Recognizing the incidence of cancer is important because it can reduce the incidence of new cancers. Prevention and early detection efforts are needed which will be easier to do when the risk factors and symptoms of cancer are identified. Breast cancer is very dangerous and must be watched out for early on. Nevertheless, breast cancer can be prevented by living a healthy lifestyle, routinely carrying out Breast Self-Examination (BSE) which is done by every woman. The purpose of the study was to describe the knowledge of young women about BSE. The study was conducted on 76 class X students, majoring in Multi Media (MM), Computer and Network Engineering (TKJ), Industrial Electronic Engineering (TEI) at SMK NU Ungaran with accidental sampling as a sampling technique. Assessment of knowledge of young women was carried out with a questionnaire about BSE examination. The research data obtained were 18 students (23.7%) had less knowledge, 25 students (32%) had good knowledge and 33 students (43%) had sufficient knowledge. Suggestions for schools are that it is hoped that the formation of peers can be an approach to assist young women in obtaining health education, especially about BSE, in collaboration with the puskesmas or the nearest health institution Abstrak Pada remaja putri terjadi tahap perkembangan yang sangat penting, yaitu perkembangan biologis dan fisiologis yang dapat menentukan kualitas diri untuk menjadi seseorang yang dewasa. Haid merupakan salah satu indikator kematangan seksual perempuan. Selama siklus haid perlu diperhatikan tentang personal hygiene selama haid dan penanganan nyeri haid. Selain hal tersebut selama siklus haid ada hal yang juga menjadi perhatian remaja yaitu deteksi dini kanker payudara, karena usia muda bukan jaminan aman dari kanker payudara. Pengenalan kejadian kanker menjadi penting karena dapat menurunkan kejadian baru kanker diperlukan upaya pencegahan dan deteksi dini yang akan lebih mudah dilakukan ketika faktor risiko dan gejala kanker sudah dikenali. Kanker payudara sangat berbahaya dan harus diwaspadai sejak dini. Meskipun demikian, kanker payudara dapat dicegah dengan perilaku hidup sehat, rutin melakukan Pemeriksaan Payudara Sendiri (SADARI) yang dilakukan oleh setiap perempuan Tujuan dari penelitian adalah untuk mengetahui gambaran pengetahuan remaja putri tentang SADARI. Penelitian dilakukan pada 76 siswi kelas X, jurusan Multi Media (MM), Tehnik Komputer dan Jaringan (TKJ), Tehnik elektronik Industri (TEI) SMK NU Ungaran dengan teknik pengambilan sampel menggunakan accidental sampling. Penilaian pengetahuan remaja putri dilakukan dengan kuesioner tentang pemeriksaan SADARI. Data hasil penelitian diperoleh sebanyak 18 siswi (23,7%) mempunyai pengetahuan kurang, sebanyak 25 siswi (32%) mempunyai pengetahuan baik dan sebanyak 33 siswi (43%) mempunyai pengetahuan cukup. Saran untuk sekolah diharapkan adanya pembentukan teman sebaya bisa menjadikan salah satu pendekatan untuk membantu remaja putri dalam mendapatkan edukasi kesehatan khususnya tentang SADARI, dengan bekerja sama dengan pihak puskesmas ataupun institusi kesehatan terdekat.